BI-RADS Breast Tumor Classification Through Image Mining - da Silva, Valesca J. S.; da Silva, Mateus M. R.; Silva, Marcelino P. S.; Nogueira, Joana R. C. (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe), 2019)
In this article, a computer aided diagnostic system for BI-RADS classification of breast cancer is proposed. The approach involves image processing capabilities to extract features from tumors in mammography and image mining to classify them as BI-RADS 2, BI-RADS 3, BI-RADS 4C or BI-RADS 5. Images from the BCDR repository were used for the experiments. The results showed the efficacy of the proposed method, which classified tumors with considerable accuracy in four BI-RADS categories.